2015
DOI: 10.1186/s13567-014-0138-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of systemic immune response markers through metabolomic profiling of plasma from calves given an intra-nasally delivered respiratory vaccine

Abstract: Vaccination procedures within the cattle industry are important disease control tools to minimize economic and welfare burdens associated with respiratory pathogens. However, new vaccine, antigen and carrier technologies are required to combat emerging viral strains and enhance the efficacy of respiratory vaccines, particularly at the point of pathogen entry. New technologies, specifically metabolomic profiling, could be applied to identify metabolite immune-correlates representative of immune protection follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Gray et al [89] identified metabolites in the plasma of calves vaccinated with an intranasally delivered respiratory vaccine. Furthermore, metabolites may play important roles as ultimate end stage products or mediators of biological processes, so the analysis of the metabolites present in bovine plasma is the result of the mucosal immune response of the host.…”
Section: New Omics Perspectivesmentioning
confidence: 99%
“…Gray et al [89] identified metabolites in the plasma of calves vaccinated with an intranasally delivered respiratory vaccine. Furthermore, metabolites may play important roles as ultimate end stage products or mediators of biological processes, so the analysis of the metabolites present in bovine plasma is the result of the mucosal immune response of the host.…”
Section: New Omics Perspectivesmentioning
confidence: 99%
“…A relatively large study with lactating Danish Holstein-Friesian and Jersey cows revealed an association between the milk metabolome and somatic cell count (Sundekilde et al 2013). Other studies have shown changes in the systemic metabolome of Holstein-Friesian calves after experimental infection (De Buck et al 2014) and vaccination (Gray et al 2015).…”
Section: Metabolome and Ketosismentioning
confidence: 97%
“…In the post-genomic era, the rapid growth in 'omic' technologies has led to a greater understanding of physiological processes within the body, allowing researchers to understand how a particular perturbation in a biological system affects up-stream and downstream biological processes A C C E P T E D M A N U S C R I P T [10,11,12]. Proteomics, in contrast to transcriptomics, has the capacity to highlight actual changes in functional protein levels and provide information not only on proteins produced within tissue of interest but also on those effector proteins originating from the circulatory system.…”
Section: Accepted Manuscriptmentioning
confidence: 99%